Revision of Southern Hemisphere Austronanus Hodgson, 1910, with two new genera and five new species of Paramunnidae (Crustacea: Isopoda: Asellota) - Just, Jean; Wilson, George D.f. (Zootaxa, 2006)
Paramunnid species of Southern Hemisphere cold-water Austronanus Hodgson, 1910 and related genera are characterised by simple, smooth, flattened, rather elongate oval bodies, a broadly projecting frontal head margin, well-developed, short, mostly distally bulging eyestalks with ommatidia, pereonites with lateral margins contiguous, rounded or truncate, and dorsally visible coxae V–VII. Just and Wilson (2004) rejected synonymy of Austronanus with Paramunna Sars proposed by Nordenstam (1933), following a revision of the latter genus. The type species, Austronanus glacialis Hodgson, 1910, is re-described based on topotypic material from McMurdo Sound, Antarctica, (the holotype is a small manca). The types of Paramunna dentata Nordenstam, 1933 and P. dubia Hale, 1937 are re-described and the two species referred to Austronanus together with three new Antarctic and subantarctic species, A. aucklandensis, A. gelidus and A. mawsoni. Paramunna patagoniensis Winkler, 1994 is redescribed and made the type species of a new genus, Xigonus. A new genus, Stephenseniellus, is established for two new species from the subantarctic islands south of New Zealand and Australia, S. palliolatipes (type species) from Macquarie Island, and S. serraticornis (originally reported by Stephensen, 1927 as “Paramunna (serrata (Richardson) ?”) from Auckland Island.